STUDI PELAKSANAAN KINERJA PERCEPATAN WAKTU PADA PROYEK PEMBANGUNAN GEDUNG BANK DARAH RUMAH SAKIT Dr. SOEDOMO - Widodo Restu Putra; Ahmad Ridwan; Yosef Cahyo; Agata Iwan Candra (Faculty of Engineering, Kadiri University, 2020)
Dr.Soedomo Trenggalek Hospital has a goal to realize an optimal service for the community through the availability of supporting infrastructures. One of them is the Blood Bank Building Hospital. This study aims to determine how much cost efficiency and time efficiency of the Blood Bank Building construction project at Dr. Soedomo Trenggalek Hospital are accelerated for seven days. The research method used is the